Словообразующие свойства глаголов со значением пространственной модификации и повторного действия - Бразaускене Е. (Kalbotyra, 1992)
This article deals with the problem of studying or word-formation from the prefixal verbs. In consequence or the analysis of locative and some other formal-semantic groups of the Russian derivative verbs we determine their derivational potentials and the factor influencing them.